2009
DOI: 10.1111/j.1468-3083.2009.03099.x
|View full text |Cite
|
Sign up to set email alerts
|

Interest of the association retinaldehyde/glycolic acid in adult acne

Abstract: These data show that a combination of RAL 0.1% and GA 6% may be used in association with other topical anti-acne treatments with an excellent tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 20 publications
(40 reference statements)
0
31
0
Order By: Relevance
“…It seems clear that there is an emerging population of individuals seeking acne treatment who are aged 25 and older with acne that is generally similar to that of adolescent acne. These are often active patients, experiencing a relatively high level of daily stress; based on adult subgroup analyses of large‐scale controlled clinical trials of various acne medications and other studies, it seems likely that these individuals will respond well to conventional acne therapy . The majority of adult women who have acne lesions report continuing or relapsing acne from adolescence, and they have often used many topical and/or systemic products.…”
Section: Discussionmentioning
confidence: 99%
“…It seems clear that there is an emerging population of individuals seeking acne treatment who are aged 25 and older with acne that is generally similar to that of adolescent acne. These are often active patients, experiencing a relatively high level of daily stress; based on adult subgroup analyses of large‐scale controlled clinical trials of various acne medications and other studies, it seems likely that these individuals will respond well to conventional acne therapy . The majority of adult women who have acne lesions report continuing or relapsing acne from adolescence, and they have often used many topical and/or systemic products.…”
Section: Discussionmentioning
confidence: 99%
“…Since low concentrations of AHA (5–10%) act on the superficial layers of the skin – by augmenting the healing response by subcorneal epidermolysis, opening comedones and unroofing pustules – many dermatologists feel that products containing AHAs should not be classified as cosmetics . However, several studies (including a large multicentre, double‐blind, randomized, vehicle‐controlled trial) have demonstrated the safety and efficacy of a preparation containing a combination of the AHA glycolic acid and retinaldehyde (a form of vitamin A) in treating acne and post‐inflammatory hyperpigmentation associated with acne . Furthermore, a recent single‐centre, double‐blind, randomized, placebo‐controlled trial on 10% glycolic acid monotherapy for mild acne showed significant improvement in acne compared with the placebo after 90 days of treatment …”
Section: Alpha‐hydroxy Acidsmentioning
confidence: 99%
“…However, in a second study there were no significant differences in effectiveness between GA and SA. 14,15 …”
Section: Resultsmentioning
confidence: 99%
“…15 Although a slight redness and swelling might be seen after treatment with GA and it's especially happens in black-skinned patients. 5,17 GA is an alpha-hydroxyl acid and works by removing the corneum stratum layer, scattering basal melanocytic layer and stimulating epidermolysis.…”
Section: Discussionmentioning
confidence: 99%